Penambahan Serbuk Kelopak Bunga Rosela (Hibiscus sabdariffa L.) untuk Meningkatkan Aktivitas Antioksidan pada Tempe Kedelai - Nopiana Elia Putri Sitanggang; Lusiawati Dewi (Faculty of Agricultural Technology, University of Jember, 2022)
Tempeh is a traditional food product made from soybeans through a fermentation process by tempeh mold (Rhizopus sp.). This food product besides having high nutritional value also contains antioxidant compounds which are very good for consumption but with a relatively low IC50 value. This study used rosella flower calyx (Hibiscus sabdariffa L.) which are believed to have a high enough antioxidant content so they are effective in increasing the antioxidant content in tempeh. Furthermore, the addition of rosella calyx powder will give tempeh an attractive taste, aroma, and color. The objective of this research was to determine the effect of rosella calyx powder addition on tempeh making with various concentrations, i.e. 0% (P0), 0.5% (P2), 1% (P3), 1.5% (P4), and 2% (P5). The antioxidant activity using the DPPH method, the organoleptic properties based on the preference level (hedonic) using a questionnaire, and the water content of tempeh based on the principle of gravimetry method were also tested. The result showed that the IC50 value of 2% concentration of rosella calyx powder addition (P5) was 1596.9 ppm. IC50 of the P5 treatment was the highest antioxidant activity power category compared the other treatment, even though it was still relatively low in antioxidant activity. Then on the organoleptic test, the results showed that the addition of rosella flower calyx powder was able to affect the taste, color, and aroma of tempeh and has no effect on the water content of tempeh. Keywords: antioxidant, organoleptic, rosella, tempeh, water content